PENERAPAN MODEL PEMBELAJARAN TGT (TEAMS GAMES TOURNAMENT) BERBANTUAN MEDIA BILIK SUMBER DAYA ALAM MATA PELAJARAN IPAS SISWA KELAS 5 SDN 03 MADIUN LOR - Saputro, Rinaldi Eko Saputro; Dewi, Candra; Dewanti, Amalya Trisuci (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The goal of this research was to find out if the fifth graders at SDN 03 Madiun Lor are more engaged in science classes when they use the Teams Games Tournament (TGT) model with the media from the natural resource booth in the 2023-2024 school year. The 28 participants in this study were all from Class 5B, and the research methodology employed was Classroom Action Research (PTK). This study utilized the Teams Games Tournament (TGT) learning model, which primarily aimed to motivate IPAS learning. The data was analyzed using descriptive statistics after data collection. Assuming the acquired score is in the moderate to high range, the success criterion can be satisfied. According to studies done by professionals in the field Researchers have shown that fifth graders at SDN 03 Madiun Lor are more likely to be interested in and successful in their social studies classes when they use the TGT learning paradigm in conjunction with media from a miniature natural resource booth. Similarly, during the 2023-2024 academic year, fifth graders at SDN 03 Madiun Lor will be more motivated to learn. This is supported by the fact that the learning motivation score increased from 78.67% in the first cycle to 84.78% in the second cycle, falling into the high category. Keywords: motivation, student, teams games turnament